Efficacy of elastodontic devices in overjet and overbite reduction assessed by computer-aid evaluation - Eleonora Ortu; Davide Pietropaoli; Samuele Cova; Maria Chiara Marci; Annalisa Monaco (BMC, 2021)
Abstract Background This study aimed to verify the efficacy of two elastodontic devices in overjet (OJ) and overbite (OB) reduction during treatment with the Equilibrator Series II (Eptamed) and Occlus-o-Guide (Sweden & Martina) devices. Method Sixty patients aged 7-15 years were enrolled in the study, and were divided into test and control groups. The test group included 30 patients (14 males, 16 females; mean age, 10.66 ± 2.12 years) treated with the EQ (Equilibrator) Series II. The control group included 30 patients (15 males, 15 females; mean age, 10.76 ± 2.52 years) treated with the Occlus-o-Guide. The two groups exhibited the same orthodontic features. The orthodontic criteria were: skeletal and dental class II malocclusion (divisions 1 and 2); and the presence of OJ and OB. Evaluation of OJ and OB was performed at two timepoints: T0 (before starting therapy) and T1 (after 1 year). Results At T0, OJ and OB were similar for the two groups; however, at T1, both OJ and OB were significantly lower with the Eptamed device compared to the Occlus-o-Guide device (p = 0.0019). Conclusions Elastodontic devices improve orthodontic outcomes by aiding orthodontic patient management, diagnosis, and treatment planning, reducing the risk relapse acting on the whole organism and the rehabilitation of the tongue.